Examining the Impact of Computer Literacy and Work Management Skills on Organizational Roles - Reyes, Ma. Josefa Sario; Coronado, Princess Zarah; Britanico, KC Baydal (The Indonesian Institute of Science and Technology Research, 2025)
This study examines the association between computer literacy and work management skills with various demographic and professional profiles among employees at the Local Government Unit (LGU) of Polangui, Albay. Chi-square tests revealed no significant differences in computer literacy and work management across age, sex, appointment status, management level, office assignment, or seminar attendance. However, significant differences were found related to the highest educational attainment and professional eligibility certifications, indicating that these factors influence the proficiency levels in computer skills and work management abilities. The findings underscore the critical role of formal education and professional certifications in enhancing workplace competencies. The study recommends targeted training and resource development to address skill disparities and improve organizational performance.